2021
DOI: 10.1111/1365-2656.13581
|View full text |Cite
|
Sign up to set email alerts
|

Optimal stopover model: A state‐dependent habitat selection model for staging passerines

Abstract: 1. During their seasonal migration, birds stage in areas comprising stopover sites of varying quality. Given that migrating birds have a limited information about their environment, they may land at a low-quality stopover site in which their fuel deposition rate (FDR) is low. Birds landing at such sites should decide either to extend their stopover duration or to quickly depart in search for a better site. These decisions, however, strongly depend on their body condition upon landing. 2. To understand the deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In this way, lactic acid, glucose, and glycerol are examples of metabolites that were previously demonstrated to vary between birds before and after resting (Viswanathan et al 1987, Jenni-Eiermann andJenni 1992). Our previous research efforts (Domer et al 2018(Domer et al , 2021 have…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In this way, lactic acid, glucose, and glycerol are examples of metabolites that were previously demonstrated to vary between birds before and after resting (Viswanathan et al 1987, Jenni-Eiermann andJenni 1992). Our previous research efforts (Domer et al 2018(Domer et al , 2021 have…”
Section: Discussionmentioning
confidence: 83%
“…In this way, lactic acid, glucose, and glycerol are examples of metabolites that were previously demonstrated to vary between birds before and after resting (Viswanathan et al 1987, Jenni-Eiermann and Jenni 1992). Our previous research efforts (Domer et al 2018, 2021) have shown that during autumn migration, both recapture and fuel accumulation rates are higher in ER than in BGS. These findings, in combination with the results presented here, strongly suggest that most birds at BGS leave soon after arrival (i.e., do not spend another night at this site) while most birds in ER are at a resting/refueling state.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the contrary, small Mediterranean islands offer a very limited variety of dry scrublands, where fuel deposition rates have been found to be lower than in large Balearic Islands 21 . Migrating passerines arriving at unfamiliar stopover areas must base their choices on instant decisions 58 and island area may be a quick and easy indicator to use. Low-quality stopover sites can act as an ecological trap, especially for migrating birds with insufficient fuel load to leave in search for an alternative place of a higher quality 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Migrating passerines arriving at unfamiliar stopover areas must base their choices on instant decisions 58 and island area may be a quick and easy indicator to use. Low-quality stopover sites can act as an ecological trap, especially for migrating birds with insufficient fuel load to leave in search for an alternative place of a higher quality 58 . Moving to an alternative stopover site may be even more costly and unpredictable when crossing the sea, thus the use of cues for improving the chance of selecting a high-quality island or avoiding low quality ones would be highly rewarding.…”
Section: Discussionmentioning
confidence: 99%